If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(1-5)2=x
We move all terms to the left:
-6(1-5)2-(x)=0
We add all the numbers together, and all the variables
-x-6(-4)2=0
We add all the numbers together, and all the variables
-1x+48=0
We move all terms containing x to the left, all other terms to the right
-x=-48
x=-48/-1
x=+48
| -7(y+2)=-5y-4 | | -8x+8-2x=88 | | -2m+6=-(4=2m) | | (4x-8)=(2x+8) | | -k=43 | | -3=-5r+4r | | 8x-12=-2x+8 | | r-8=62 | | 16w-24=160 | | -55=3n+4(n-5) | | 6r^2-5r-14=0 | | 5r+(3r-1)=-46 | | T=4s+1 | | -25x-5=7 | | 9x-4-3x+2=90 | | -9y=46 | | -18+19q=q-20+18q | | 3(2x-1)=2(2x+5) | | -16x^2+96x+2.5=0 | | -11=-2+b | | 23-3+12x+8=180 | | -2(x+6)=-3(x+4) | | 3(-4r+r)=27 | | 16w+24=160 | | x-2=4x+5 | | -3x+6x=11x-2 | | 2(4x-9)=-42 | | 2/3+3/5m=36/15 | | -4v=-2-6v | | 19.30=(13.4+x)-10 | | 0.25x–19.5=–13.5 | | 0.04(m+10)+0.06(m-30)=7.6 |